Determinasi Firm Value: Investigasi Pengaruh Dividend Payout Ratio, Debt-to-Equity Ratio, Investment Opportunity Set, dan Inflasi - Nurhalimah; Rifani Akbar Sulbahri; Aida Rakhmawati (Fakultas Ekonomi Universitas Tridinanti Palembang, 2024)
Abstract : The research to determine the contemporaneous, partially significant effects includes the subsequent factors on firm value in infrastructure companies: dividend payouat ratio, debt to equity ratio, investment opportunity set, dan inflasion. The research sample consists of the sixteen infrastructure companies that were listed on the IDX between 2019 and 2022. This study made use of secondary data that is available at http;//www.idx.co.id. Purposeful sampling was used as the sample technique. The variables of the study were computed using a computer and SPSS 25. According to the findings, the four variales dividend payout ratio, debt to equity ratio, investment opportunity set, and inflation—all concurrently had a substantial influence on the worth of the enterprise. The outcomes of a partial hypothesis test demonstrates that the firm vaue is significantly impacted by the debt to equity ratio and the investment opportunity set. Abstrak : Pengujian ini untuk mengetahui sejauh mana dividend payouat ratio, debt to equity ratio, investment opportunity set, dan inflasi secara signifikan, simultan, dan parsial mempengaruhi firm value pada perusahaan infrastruktur. 16 perusahaan infrastruktur yang terdaftar di BEI periode 2019-2022. Data sekunder dapat diakses di http://www.idx.co.id. Purposive sampling diaplikasikan sebagai teknik sampel. Variabel dalam penelitian ini dihitung dengan menggunakan komputer dan software SPSS 25. Temuan riset menunjukkan bahwa empat faktor yang secara bersamaan mempunyai dampak besar terhadap nilai perusahaan adalah dividend payout ratio, debt to equity ratio, investment opportunity set, dan inflasi. Temuan pengujian hipotesis secara parsial menunjukkan bahwa debt to equity ratio dan investment opportunity set mempunyai pengaruh terhadap nilai perusahaan, sedangkan dividend payout ratio dan Inflasi tidak mempunyai pengaruh terhadap firm value.